Communication Style of Instagram Account Followed by Millennials - Ade Namira; Umar Mono; Alemina Br. Perangin-angin (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2022)
This study investigated the communication style used by an Instagram account to engage millennials. A qualitative approach with document study was used. This shows Instagram posts are part of the personal documents that can be analyzed based on types of communication styles. The source of data was the Folkative Instagram account which has approximately 6000 postings with a hundred thousand likes and thousands of comments. In this study, ten captions were taken as the data. The data were analyzed through data collection, data reduction, data display, and conclusion drawing. The result found three communication styles were used by Folkative namely structuring style, equalitarian style, and controlling style. To sum up, Folkative engages the millennials through structuring style, equalitarian style, and controlling style.